Unsteady MHD Free Convection by Passing Cobalt Nanoparticles Past an Accelerated Vertical Plate Through Porous Medium of Ethylene Glycol - G. Vijaya Kumar, A.; Vankudre, M.; Mirajgaonkar, N.; Bagwe, K. (International Journal of Engineering and Technology, 2018)
This article studies , the effects of unsteadyÂ  magneto-hydrodynamic boundary layer when cobalt nanoparticles where passed onto a vertical plate which is given an impulse by exponential acceleration through porous medium of ethylene glycol when thermal radiation is present ,parameters of absorption of heat and radiation, chemical reaction parameter, magnetic field in transverse direction are theoretically studied. We consider cobalt nanoparticles resembles to spherical structure and range of volume of nanoparticle concentration is basically less than or equal to 4%. Considering the boundary conditions we have formulated a governing equations of nanoparticles which is in the form of partial differential equations. The precise solutions for velocity, concentration and temperature profiles are obtained by plotting the graphs of the equations formed using Laplace Method using MATLAB software. This study of heat transfer in nanoparticles finds application in tribological aspect, biological fields dealing with molecular level cell interactions, improving thermal conductivity and commercial cooling applications. The most significant outcome of this study is found in the concentration profile where time is varied. We see that there is 68% decrease in concentration when the time interval chosen is 0.2, whereas the decrease is found to 55% when the interval is increased to 0.4 keeping the distance from vertical plate constant.Â Â